How Much Do Corporate Defendants Really Lose? A New Verdict on the Reputation Loss Induced by Corporate Litigation. Issue 2 (9th March 2017) - Haslem, Bruce; Hutton, Irena; Smith, Aimee Hoffmann
Abstract : Using a novel sample of 83, 260 lawsuits filed in US Federal District courts, we extend the results of prior studies investigating market value and reputational losses due to corporate misconduct. We examine alternative explanations for the loss in market value, such as media coverage, the expectation of subsequent litigation, and the defendant's willingness to settle, in addition to previously documented factors. Our results suggest that with the exception of securities litigation, this loss in market value can be attributed to these alternative explanations rather than to reputational consequences. This finding is confirmed by several indirect measures of reputation loss.